2010
DOI: 10.1111/j.1750-3841.2010.01599.x
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effect of Salt‐Free Soy Sauce, a New Fermented Seasoning, in Spontaneously Hypertensive Rats

Abstract: In this study, we investigated the antihypertensive effect of newly fermented SFS in SHRs. As a result of 13-wk SFS-administration, we found a significant antihypertensive effect of the SFS. This finding strongly demonstrates that the developed SFS would be greatly beneficial for health and useful for health-related industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Fermented foods such as fermented salt-free soy sauce and Korean fermented soybean paste have been shown to significantly decrease BP in rats [33,34]; however, evidence from human trials is insufficient to suggest that fermented foods lower BP in humans. We previously reported that consumption of fermented kimchi had a greater effect on systolic and diastolic BP in overweight and obese patients than did fresh kimchi [10].…”
Section: Discussionmentioning
confidence: 99%
“…Fermented foods such as fermented salt-free soy sauce and Korean fermented soybean paste have been shown to significantly decrease BP in rats [33,34]; however, evidence from human trials is insufficient to suggest that fermented foods lower BP in humans. We previously reported that consumption of fermented kimchi had a greater effect on systolic and diastolic BP in overweight and obese patients than did fresh kimchi [10].…”
Section: Discussionmentioning
confidence: 99%
“…Antihypertensive activity has been proved in protein hydrolysates and peptides generated from sources such as rice,4 and soy sauce 5. Since hypertension is related to cardiovascular diseases (ateriosclerosis, stroke and myocardial infarction) and end‐stage renal disease, the intake of these peptides could reduce the risk of developing these types of illness.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, antihypertensive agents were suggested by various mechanisms. Inhibition of angiotensin I converting enzyme (ACE), one of antihypertensive mechanism, has been used for evaluating antihypertensive activity of natural products and functional food [21]. ACE removes a dipeptide from the C terminus of angiotensin I to form angiotensin II, a highly reactive hypertensive compound [20].…”
Section: Resultsmentioning
confidence: 99%